Analisis Pengelolaan Sumber Daya Alam Sebagai Sumber Pendapatan Ekonomi Masyarakat Lokal di Sempadan Sungai Rungan Kota Palangka Raya: Analysis of Natural Resource Management a Resource - Nawan Kurniawan; Riki Cahyadi; Phebe Tamariska; Dedi Takari (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The Rungan River area in Palangka Raya City has abundant natural resources potential, including fisheries, agriculture, and other resources. The local community heavily relies on these natural resources as their main source of livelihood. This research examines the management of natural resources in the area as a source of economic income for the local community by combining descriptive and qualitative methods. The research findings show that the community possesses local wisdom in managing and preserving natural resources, such as Pasah Patahu, Santo Nazar, and technology-based management. However, there are still challenges, such as suboptimal utilization of natural resources, lack of support from the government and related institutions, and underutilization of technology. Further efforts from various parties are needed to optimize the management of natural resources in order to sustainably increase the economic income of the local community.